Petra University’s Students’ Uses For SMS Messages and its Verifications (A Field Study on Students of Petra University’s Colleges) - Tahat, Zurair Yasin; Al-Dubaisi, Abdulkarim Ali; Al-Qudhat, Muhammed Falah (ALBAHITH ALALAMI, 2014)
This study aims at identifying the extent of SMS usage and understanding the role it plays in satisfying users’ needs and motivations. In order to achieve this aim, an analytical descriptive method was adopted by conducting a field survey among students at Petra University. The study resulted in many conclusions, the most important of which is that using SMS meets the students’ cognitive, social and communicational needs and desires, the highest being communicating with friends at 75%, followed by exchanging songs and videos at 52%, as well as exchanging photos at 45%. In regards to their motivation for using text messaging, forgetting daily problems scored highest at 81.4% and spending free time followed at 77.4%. This proves that using mobile phones and SMS fulfills certain needs and motivations for the sample studied. Moreover, the research emphasizes the importance of the role that the Higher Ministry of Education in Jordan should have in launching campaigns to educate students and draw their attention to the negative side effects that using mobile phones during classes and lectures has on the educational process